2001
DOI: 10.1054/bjoc.2001.2178
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin as a prognostic indicator in primary breast cancer

Abstract: Summary Epithelial cadherin (E-CD) is a member of the cadherin family of cell adhesion molecules and has been implicated as an invasion suppressor molecule in vitro and in vivo. We analysed 174 breast tumours from the Nottingham/Tenovus Breast Cancer Series immunohistochemically for E-CD expression using the mouse monoclonal antibody HECD-1 (Zymed Laboratories Inc.). In normal epithelial cells E-CD was strongly expressed at cell-cell boundaries. 66% of the breast cancers examined had reduced intensity of E-CD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 22 publications
6
61
1
1
Order By: Relevance
“…Furthermore, node-negative and nodepositive tumours exhibited similar E-cadherin expression and no correlation between E-cadherin expression and metastatic status was observed. A number of additional reports show similar results regarding E-cadherin expression and tumour aggressiveness, implying that invasion is not necessarily dependent on a complete transition to a mesenchymal phenotype (Parker et al, 2001;Kovacs et al, 2003). Barrallo-Gimeno and co-workers argued that the primary function of Snail is to enhance cell movement, rather than to induce EMT (Barrallo-Gimeno and Nieto, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, node-negative and nodepositive tumours exhibited similar E-cadherin expression and no correlation between E-cadherin expression and metastatic status was observed. A number of additional reports show similar results regarding E-cadherin expression and tumour aggressiveness, implying that invasion is not necessarily dependent on a complete transition to a mesenchymal phenotype (Parker et al, 2001;Kovacs et al, 2003). Barrallo-Gimeno and co-workers argued that the primary function of Snail is to enhance cell movement, rather than to induce EMT (Barrallo-Gimeno and Nieto, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…39,40 In ductal carcinomas of the breast, immunohistochemical studies have not demonstrated any apparent correlation of E-cadherin expression with the scattered morphology, tumor type, nodal status, disease recurrence, distant metastases, or other prognostic factors. [41][42][43][44] These observations suggest that a complete transition to a mesenchymal phenotype associated with transcriptional switching is not required for increased malignancy. Most advanced carcinomas may display some mesenchymal features but still retain well-differentiated epithelial cell characteristics.…”
Section: Discussionmentioning
confidence: 92%
“…Tumors, all with neoplastic cellularity greater than 50%, were obtained with appropriate ethical approval and are detailed in Supplementary Tables 2 and 3. The breast tumors were primary operable invasive breast cancers from the Nottingham City Hospital Tumor Bank (Elston and Ellis, 1991;Parker et al, 2001;Miremadi et al, 2002). Ovarian tumors were from Addenbrooke's Hospital, Cambridge.…”
Section: Primary Tumors and Cell Linesmentioning
confidence: 99%